Low cost high-efficiency high-density-plasma Silicon-based thin film solar cells with high light-soaking stability - Hsiao, T. H.; Shieh, J. M.; Yu, P. C.; Shen, C. H.; Kao, M. H.; Chiou, U. P.; Hsieh, W. H. (My University, 2012)
We investigate the performance of a single-junction amorphous Si (a-Si) and a-Si/a-Si tandem solar cells fabricated with Inductively Coupled Plasma (ICP) deposition technique. The high-density plasma resulting from high dissociation capacity of ICP enables good-quality hydrogenated Si films to be synthesized at low temperatures. High-density ICP also promotes the diffusion of reactive radicals on substrates and forms a-Si:H films with low defect density. We demonstrate single-junction a-Si solar cells and a-Si/a-Si tandem solar cell with a conversion efficiency of 9.6% and 8.8%, respectively. Highly light-soaking stable high-density plasma-fabricated a-Si and a-Si/a-Si solar cells were demonstrated with photo-induced degradation in conversion-efficiency as low as 7% and 5%, respectively.
Keywords: amorphous silicon; ICP-CVD; photovoltaic cells